Investigating the Effects of the Leadership Styles Used by Physical Education and Sports Teachers on Classroom Management Behaviors (Diyarbakir Province Example) - Tan, Çetin; Altınay, Tayfun (İbrahim ERDEMİR, 2024)
Aim: The purpose of this study is to reveal the relationship between the leadership styles of physical education and sports teachers and their classroom management behaviors Methods: The universe of the study consisted of 921 physical education and sports teachers working in Diyarbakır province in the 2022-2023 academic year. The sample of the study consisted of 300 physical education and sports teachers randomly selected from the universe. In order to collect data in the study; Personal Information Form, Teacher Leadership Styles Scale and Classroom Management Behaviors Scale were used. Licensed SPSS 22 package program was used in the analysis of the data. Independent samples t-test was used in the study, and one-way analysis of variance (ANOVA) was used in the comparison of more than two groups. In addition, Tukey test was performed to determine the source of the difference obtained from the one-way analysis of variance (ANOVA) results. Finally, multiple regression analysis was performed. Results: According to the research findings, teachers with a democratic/participative leadership style have more positive classroom management behaviors compared to teachers with semi-democratic and autocratic/oppressive leadership styles. On the other hand, teachers with a semi-democratic leadership style exhibit more positive classroom management behaviors compared to teachers with autocratic/oppressive leadership styles. Finally, teachers with an autocratic/oppressive leadership style exhibit more negative classroom management behaviors compared to teachers with semi-democratic and democratic/oppressive leadership styles. Male teachers exhibit relatively more negative classroom management behaviors compared to female teachers. Conclusion: Democratic leadership style is the most ideal approach for classroom management. This style helps to understand students' needs, increase their participation, and gain student satisfaction while maintaining order. Semi-democratic leadership is more effective than autocratic leadership, but it does not have as strong an effect as full democratic leadership. Gender differences affect teachers' attitudes and behaviors in classroom management. The more positive behaviors of female teachers may be related to their adoption of a more student-centered approach.

Amaç: Bu çalışmanın amacı beden eğitimi ve spor öğretmenlerinin liderlik stilleri ile sınıf yönetimi davranışları arasındaki ilişkinin ortaya konulmasıdır. Gereç ve Yöntem: Araştırmanın evrenini 2022-2023 eğitim-öğretim yılında Diyarbakır ilinde görev yapan 921 beden eğitimi ve spor öğretmeni oluşturmuştur. Araştırmanın örneklemini ise evren içerisinden rastgele seçilen 300 beden eğitimi ve spor öğretmeni oluşturmuştur. Çalışmada veri toplamak amacıyla; Kişisel Bilgi Formu, Öğretmen Liderlik Stillleri ölçeği ve Sınıf Yönetimi Davranışları ölçeği kullanılmıştır. Verilerin analizinde Lisanslı SPSS 22 paket programı kullanılmıştır. Anlamlılık P
Beden Eğitimi ve Spor Öğretmenlerinin Kullandıkları Liderlik Stillerinin Sınıf Yönetimi Davranışlarına Olan Etkilerinin İncelenmesi (Diyarbakır İli Örneği)
Keywords: Sports Science and Exercise (Other); Egzersiz ve Spor Bilimleri (Diğer)